Analisis Edible Film dari Campuran Keratin dan Pati Jagung - Rina Mirdayanti; Basuki Wirjosentono; Eddy Marlianto (Fakultas Teknik, 2018)
The objectives of this research are to know the physical characteristics (water vapor transmission rate, water absorption), mechanical characteristics of edible film (maturation, tensile strength), morphology(functional group) and the edible film thermal properties made of corn starch and keratin. In this research, keratin extraction method of chicken feather waste is continued to know the influence of keratin preparation as filler material. Keratin concentration was used for each variation with comparison to corn starch matrix with keratin ie 0%, 3%, 5%, 7% and 9%. In the research used type sorbitol plasticizer which is a sugar substitutecompound that is non toxin. The data obtained from the results of the study in the analysis to see the properties of feeding for food packaging with a low rate of water vapor transmission with a value of 0.00334 g / cm2 / day. From the testing of mechanical properties for tensile strength and elongation, the optimum percentage of keratin addition was 9% whose values were 25.02 MPa and 3.64% respectively. Thermal analysis and functional groups with the addition of keratin increase the melting temperature and decomposition temperature by mixing physically. From all tests, the best percentage of keratin addition was found on the 9% keratin composition.